Analyses of sphingosine‐1‐phosphate in the context of transfusion: how much is in stored blood products and in patient blood?. Issue 10 (4th September 2019) - Poppe, Annika; Moritz, Eileen; Geffken, Maria; Schreiber, Joerg; Greiwe, Gillis; Amschler, Katharina; Wruck, Marie‐Louise; Schwedhelm, Edzard; Daum, Günter; Kluge, Stefan; Peine, Sven; Winkler, Martin Sebastian
Abstract : BACKGROUND: Sphingosine‐1‐phosphate (S1P) is a bloodborne lipid that regulates vascular tone and endothelial permeability. S1P concentrations are reduced in critically ill patients. As hematopoietic cells produce S1P, this study intends to investigate S1P concentrations in blood products during storage and in patient plasma after blood transfusion. STUDY DESIGN AND METHODS: S1P concentrations were measured in 83 red blood cell (RBC) units and 73 platelet concentrates (PCs) before and after storage. In addition, 26 critically ill patients who received one or two RBC units were recruited to measure S1P plasma levels before and three times within 24 hours after transfusion. RESULTS: The highest S1P concentrations were found in fresh PCs. S1P concentrations in PCs are reduced by 60% when stored at room temperature for 4 days, whereas in RBCs S1P concentrations remained stable when stored at 4°C within 35 days. S1P concentrations in PCs and RBCc were 2.5 to 6 times higher compared to patient plasma. Plasma S1P levels in critically ill patients, however, transiently decreased after transfusion of RBCs and recover to pretransfusion values within the following 24 hours. CONCLUSION: S1P concentrations in blood products are significantly higher compared to human plasma S1P levels, even though plasma S1P levels decreased after RBC transfusion in critically ill patients and reached pretransfusion values within 24 hours.